The Influence of Application of Local-wisdom-based Modules toward Peace-loving Characters of Elementary School Students - Asrial; Syahrial; Dwi Agus Kurniawan; Alirmansyah; Muhammad Sholeh; Muhammad Dewa Zulkhi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
The purpose of this study was to compare the application of printed modules and electronic modules based on local wisdom of ngubat padi to see indicators of the Peaceful Love character. This type of research is quantitative research. This study used a sample of 44 students in class VA and class V B at SDN 76/I Sun-gai Buluh. Data analysis used descriptive and inferential statistics. The peace-loving character of students can be seen in the application of electronic modules and print modules. From the two teaching materials, the peace-loving character of students with the application of the E-Module is dominant in the very good category, while the peace-loving character of students with the application of the printed module is domi-nantly good.